Konsep Penataan Destinasi Wisata Alam Puncak Dulamayo - Lydia Surijani Tatura; Rahma K. Gani (Universitas Negeri Gorontalo, 2021)
Puncak Dulamayo Nature Tourism, which is located in Gorontalo Regency, Gorontalo Province, is one of the favorite tourist attractions since it opened at the end of 2017. However, it was not well managed and organized, the location lacked several facilities such as inadequate parking space, lack of lodging, landscape furniture was still very lacking, there were no playground facilities for children and other facilities. This research aims to arrange of the Dulamayo peak natural tourism area were carried out by applying the principles of Tropical Architecture, by utilizing contoured land. This study used descriptive qualitative and quantitative research methods. Collecting data through literature review and direct observation in the field and interviews. The data was collected using literature review, interviews, and direct observation in the field. The results showed that the concept of managing and organizing the Puncak Dulamayo Nature Tourism destination with the principles of Tropical Architecture could be used as a reference in developing the Puncak Dulamayo Nature Tourism Area as one of the natural tourism destinations which could become a tourism attraction in Gorontalo Province.